Insulation’s Impact on Cutting Commercial Energy Use: A Case Study in Kabul City - Rasuli, Mohammad Azim; Torii, Shuichi (Technium Sustainability, 2023)
Buildings have an impact, on the environment as they consume an amount of energy and contribute to greenhouse gas emissions. This directly affects air quality and contributes to global warming. It is essential to shift from building designs to ones in order to reduce energy usage, lower emissions improve air quality and fight against climate change. While many countries have already embraced design practices, underdeveloped regions like Kabul in Afghanistan face challenges due to population growth and unregulated construction. This has resulted in sustainability issues. Compromised air quality. The building sector is responsible for 40% of energy consumption and is a major contributor to greenhouse gas emissions making its impact on the environment significant. To address these challenges caused by buildings there are keys needed. This study specifically focuses on one solution; insulating buildings. Insulation is recognized as a method for enhancing energy efficiency especially considering the increasing costs of energy and the necessity of supporting climate improvement initiatives worldwide. The research dives into the analysis of a 6-story building with no insulation having single glazed windows with aluminium frames that are oriented north to south. The building relies on air conditioning, for heating and cooling purposes. By comparing the energy consumption under insulated and uninsulated conditions this study conducts an extensive analysis of different thickness levels of polystyrene insulation. In the end the research emphasizes the advantages of installing insulation in building walls. It highlights that this action greatly improves the comfort of temperature while significantly lowering energy usage by 30 to 50 percent in the building that was studied.